2014
DOI: 10.3390/mi5041061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Power on the Quality of Drilled Micro Hole Using Cu50Zr50 Amorphous Alloys Foils

Abstract: Abstract:The rapid growth of the micro-electro-mechanical systems (MEMS) is being driven by the rapid development of the micro manufacturing processes. Laser beam machining is one of the micro manufacturing processes which can shape almost all ranges of engineering materials. In this study, the effect of laser power on the quality of drilled micro holes using Cu50Zr50 amorphous alloys foils is experimentally investigated. It indicates that both entrance and exit circularities diameters increase with laser powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Quintana et al [7] fabricated 47 mm diameter of microholes on Ni 78 B 14 Si 8 with 40 μm thickness by microsecond and picosecond laser processing. Wang et al [8,9] studied the microtribological behavior of Cu 50 Zr 50 amorphous alloy foil and the effect of process parameters on the microhole quality. The results showed that laser drilling technology cannot change the amorphous structure of amorphous alloys, and no cracks were observed on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Quintana et al [7] fabricated 47 mm diameter of microholes on Ni 78 B 14 Si 8 with 40 μm thickness by microsecond and picosecond laser processing. Wang et al [8,9] studied the microtribological behavior of Cu 50 Zr 50 amorphous alloy foil and the effect of process parameters on the microhole quality. The results showed that laser drilling technology cannot change the amorphous structure of amorphous alloys, and no cracks were observed on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there are many common technologies to machine micro holes, such as mechanical drilling, lasers, punching, electrical discharging machining (EDM), etc., but they all have some drawbacks such as machining stress, tool wear, and taper problems [1,2,3,4]. Electrochemical machining, as one of the most promising machining technologies, can be used to machine micro holes [2].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Investigated the effects of CO2 laser irradiation on limestone included heavy and light oil of Iran Sarvak formation. They studied the amount of laser beam absorption by this oils for determining thermal fractured during the laser drilling laboratory process [4] investigated experimentally the effect of laser power on the quality of drilled micro holes using Cu50Zr50 amorphous alloys foils. They showed that the taper of drilled holes increased quickly to a stable value with the increase of laser power from 60 to 110 W, then decreased quickly when the laser power became larger than 170 W. [13] studied Cutting of stainless steel with fiber using CO2 laser.…”
Section: Introductionmentioning
confidence: 99%